2015
DOI: 10.1002/2015gl064595
|View full text |Cite
|
Sign up to set email alerts
|

Electric field of the power terrestrial sources observed by microsatellite Chibis‐M in the Earth's ionosphere in frequency range 1–60 Hz

Abstract: The power line emission (PLE) 50/60 Hz and the Schumann resonance (SR) harmonics were detected by the use of a compact electrical field sensor of length 0.42 m during microsatellite Chibis‐M mission in years 2012–2014. The initial orbit of Chibis‐M has altitude 500 km and inclination 52°. We present the space distribution of PLE and its connections with the possible overhead power lines. PLE has been recorded both in the shade and sunlit parts of the orbits as opposed to SR which have been recorded only in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 25 publications
0
19
0
2
Order By: Relevance
“…the discussion in Ref. 4)and are still poorly understood. PLHR is formed by electromagnetic waves radiated by electric power systems on the ground at harmonic frequencies of 50 or 60 Hz mains.…”
Section: A Technical and Scientific Objectivesmentioning
confidence: 97%
“…the discussion in Ref. 4)and are still poorly understood. PLHR is formed by electromagnetic waves radiated by electric power systems on the ground at harmonic frequencies of 50 or 60 Hz mains.…”
Section: A Technical and Scientific Objectivesmentioning
confidence: 97%
“…Indeed, Plyasov et al (2012), using a simplified multi-layered plane model, estimated analytically the IAR excitation rate by an atmospheric electric discharge, and claimed the possibility of IAR detection in the midand high-latitude ionosphere by modern electric or magnetic sensors onboard low-orbiting satellites. The effective leakage of 50/60 Hz emission from industrial power lines found by microsatellite Chibis-M also indicates an effective coupling of near-surface ULF-ELF emitters with emissions in the upper ionosphere (Dudkin et al, 2015).…”
Section: Introduction: Ulf Resonators and Waveguides In The Terrestrimentioning
confidence: 97%
“…These waves can then propagate downward to the Earth (Chum & Santolík, ; Santolík & Parrot, , , ; Santolík, Chum, et al, ; Santolík et al, ). Alternatively, they may be of an artificial origin, such as electromagnetic signals from VLF transmitters (Cohen & Inan, ; Starks et al, ;) or power line harmonic radiation (e.g., Dudkin et al, ; Němec et al, , ). Finally, they may also be generated by lightning discharges.…”
Section: Introductionmentioning
confidence: 99%